2015
DOI: 10.1155/2015/406261
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Effects of Meditation Based on Evoked and Event Related Potential Recordings

Abstract: Evoked potentials (EPs) are a relatively noninvasive method to assess the integrity of sensory pathways. As the neural generators for most of the components are relatively well worked out, EPs have been used to understand the changes occurring during meditation. Event-related potentials (ERPs) yield useful information about the response to tasks, usually assessing attention. A brief review of the literature yielded eleven studies on EPs and seventeen on ERPs from 1978 to 2014. The EP studies covered short, mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Due to the advances in digital data gathering, the study of evoked potentials (EP)/event related potentials (ERP) emerged as new analysis method, complementary to spectral analysis. The distinction between them is that EP are spontaneously evoked, in contrast to ERP which are elicited by cognitive task processing (Singh Nilkamal and Telles Shirley, 2015 ). In EP/ERP a characteristic and reproducible waveform, that is time-locked with an external or internal stimulus, is recorded from the scalp (Chiappa, 1997 ; Pfurtscheller and Da Silva, 1999 ).…”
Section: Evoked Potentials/event Related Potentialsmentioning
confidence: 99%
“…Due to the advances in digital data gathering, the study of evoked potentials (EP)/event related potentials (ERP) emerged as new analysis method, complementary to spectral analysis. The distinction between them is that EP are spontaneously evoked, in contrast to ERP which are elicited by cognitive task processing (Singh Nilkamal and Telles Shirley, 2015 ). In EP/ERP a characteristic and reproducible waveform, that is time-locked with an external or internal stimulus, is recorded from the scalp (Chiappa, 1997 ; Pfurtscheller and Da Silva, 1999 ).…”
Section: Evoked Potentials/event Related Potentialsmentioning
confidence: 99%
“…Several studies conducted during the last 20 years have shown that the presence and temporal dynamics of EEG microstates are modulated by different levels of consciousness (Brodbeck et al, 2012;Katayama et al, 2007;Singh and Telles, 2015), and diseases [e.g., in schizophrenia (Kindler et al, 2011;Lehmann et al, 2005;Strelets et al, 2003)]. What is largely missing is a reliable identification of the neuronal sources generating these different EEG states, that is, the brain areas that are synchronized with each other during each of these microstates.…”
Section: Introductionmentioning
confidence: 99%
“…Event-related brain potentials (ERPs), known for their optimal temporal resolution on the millisecond scale, can provide information regarding the discriminative ability of the brain and neurocognitive processing related to shifting attention (Singh and Telles, 2015 ). ERPs can monitor the neural processes engaged in disrupted cognitive function and can identify specific neurocognitive deficiencies in mental patients (Campanella, 2013 ; Delle-Vigne et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%